First detection of Echinococcus multilocularis in golden jackals (Canis aureus) in Bosnia and Herzegovina - Naida Kapo; Jasmin Omeragić; Azra Bačić; Šejla Goletić; Adis Softić; Vedad Škapur; Toni Eterović; Jasna Salkić; Teufik Goletić (International Journal for Parasitology: Parasites and Wildlife)
Echinococcus multilocularis, the causative agent of alveolar echinococcosis (AE), is a parasitic zoonosis of increasing public health significance in Europe. Although previously confirmed in red foxes in Bosnia and Herzegovina, this study provides the first report of E. multilocularis in golden jackals (Canis aureus) in the country. Between December 2024 and March 2025, a total of 44 golden jackals were examined across 15 localities in Bosnia and Herzegovina, with E. multilocularis detected in 6.8 % of the samples from three sites in Western and Central Bosnia and Herzegovina. Adult Echinococcus spp. worms were first detected using the intestinal scraping technique and identified by microscopy. To confirm these findings and differentiate between Echinococcus species, DNA extracted from adult worms was then subjected to species-specific PCR targeting a fragment of the mitochondrial 12S ribosomal RNA gene. PCR-positive samples for E. multilocularis were further validated by next-generation sequencing (NGS) of a 203 bp amplicon of the 12S rRNA gene. These findings indicate an expanding distribution of E. multilocularis in Bosnia and Herzegovina, highlighting the role of golden jackals as definitive hosts for the parasite. Given the growing jackal population in the country and the increasing public health concerns, enhanced surveillance and further research are warranted, particularly regarding human cases of E. multilocularis infection, to better understand the associated epidemiological risks.